Answer:
y + 0.5 = 3(x - 2)
y + 0.5 = 3x - 6
y = 3x - 6.5
Step-by-step explanation:
Answer:
$10 coins: 21
$20 coins: 24
Step-by-step explanation:
heyy me again
So we can create 2 equations where
x = number of $10 coins
y = number of $20 coins:
x + y = 45
10x + 20y = 690
we can move equation 1 around so that we can get a value of x
x = 45 - y
now we can substitute x into the second equation
10(45 - y) + 20y = 690
450 - 10y + 20y = 690
10y = 240
y = 24
Now plug in y back into the first equation
x = 45 - y
x = 45 - 24
x = 21
Answer:
please mark as brilliant thanks
The get (x-1)(x-√2)(x+√2)(x-√3)(x+√3).
Expanding, you get x^5-x^4-5x^3+5x^2+6x-6.